2016
DOI: 10.1080/07391102.2016.1162751
|View full text |Cite
|
Sign up to set email alerts
|

Determination on the binding of thiadiazole derivative to human serum albumin: a spectroscopy and computational approach

Abstract: 4-[3-acetyl-5-(acetylamino)-2,3-dihydro-1,3,4-thiadiazole-2-yl]phenyl benzoate from the family of thiadiazole derivative has been newly synthesized. It has good anticancer activity as well as antibacterial and less toxic in nature, its binding characteristics are therefore of huge interest for understanding pharmacokinetic mechanism of the drug. The binding of thiadiazole derivative to human serum albumin (HSA) has been investigated by studying its quenching mechanism, binding kinetics and the molecular distan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 35 publications
2
24
0
Order By: Relevance
“…Secondary structure calculations were carried out using the DichroWeb (http://dichroweb.cryst.bbk.ac.uk/html/home. shtml) online tool for the free HSA that consists of ∼54.2% α-helix, ∼22.1% β sheets, and 16.3% of the random coil, which are almost comparable with previously published data [17,24].…”
Section: Circular Dichroism (Cd) Spectral Analysissupporting
confidence: 86%
See 2 more Smart Citations
“…Secondary structure calculations were carried out using the DichroWeb (http://dichroweb.cryst.bbk.ac.uk/html/home. shtml) online tool for the free HSA that consists of ∼54.2% α-helix, ∼22.1% β sheets, and 16.3% of the random coil, which are almost comparable with previously published data [17,24].…”
Section: Circular Dichroism (Cd) Spectral Analysissupporting
confidence: 86%
“…e emission spectrum of HSA (1 µM) and various concentrations of the coumarin derivative (0-3.6 µM) is shown in Figure 2(a), and it is indicated that there is a decrease without a shift in emission maximum of the HSA-coumarin derivative complex. Hence, we may conclude that fluorescence quenching occurs due to the presence of the coumarin derivative [17].…”
Section: Fluorescence Spectroscopy Studiesmentioning
confidence: 90%
See 1 more Smart Citation
“…The binding of CDX enantiomers in HSA subdomain IIIA present differences concerning the number of hydrogen interactions. For example, the complex ( R )-CDX1-HSA is stabilized by three hydrogen-bond interactions with residues Leu-430, Ser-489, and Asn-391, already described as being involved in the binding of drugs to HSA [57,58,59], whereas (S)-CDX1 lacks those interactions (Figure 3B). Therefore, there is concordance between in silico and in vitro studies, as enantiosselectivity can be found on the binding of CDX1 to HSA.…”
Section: Resultsmentioning
confidence: 94%
“…4‐[3‐Acetyl‐5‐(acetylamino)‐2‐methyl‐2,3‐dihydro‐1,3,4‐thiadiazole‐2‐yl]phenyl benzoate (thiadiazole derivative) drug was synthesized according to the previous literature already reported (Figure ).…”
Section: Methodsmentioning
confidence: 99%